2018
DOI: 10.1002/ajmg.a.38842
|View full text |Cite
|
Sign up to set email alerts
|

A recognizable phenotype related to 19p13.12 microdeletion

Abstract: Submicroscopic deletions in chromosome 19 have been rarely reported. We reported a male patient presenting with neurodevelopmental delay and facial dysmorphisms with a de novo 19p13.11p13.12 deletion of approximately 1.4 Mb. To date, there are seven cases with deletions overlapping the 19p13.11-p13.12 region described in the literature. A region of 800 kb for branchial arch defects in the proximal region of 19p13.12, and another minimal critical region of 305 kb for hypertrichosis, synophrys, and protruding fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similarly, diminished interactions were detected with GANAB, AKAP8L, and EIF3B across all examined variants (Figure S5). Prior reports have associated the gene dosage of AKAP8L with the microcephaly phenotype in humans 42,43 , suggesting that AKAP8L could play a role in the microcephaly phenotypes identified in our subjects. Future investigations focusing on these proteins are expected to offer a more comprehensive understanding of genotype-phenotype correlations for HDAC3-related syndromes.…”
Section: Discussionmentioning
confidence: 51%
“…Similarly, diminished interactions were detected with GANAB, AKAP8L, and EIF3B across all examined variants (Figure S5). Prior reports have associated the gene dosage of AKAP8L with the microcephaly phenotype in humans 42,43 , suggesting that AKAP8L could play a role in the microcephaly phenotypes identified in our subjects. Future investigations focusing on these proteins are expected to offer a more comprehensive understanding of genotype-phenotype correlations for HDAC3-related syndromes.…”
Section: Discussionmentioning
confidence: 51%
“…It has been reported that haploinsufficiency of BRD4 is associated with Cornelia de Lange syndrome (CdLS), a severe multisystem neurodevelopmental disorder presenting with HL as one of the clinical phenotypes (Olley et al, 2018). Similarly, a novel 2.52 Mb microdeletion at 19p13.12 that includes BRD4 was also reported in a patient presenting with HL, using high resolution chromosomal microarray analysis (de Souza et al, 2018). In addition, BRD4 and P-TEFb were identified as WHSC1 interacting partners, and together they facilitate transcriptional elongation (Sarai et al, 2013) WHSC1-deficient mice fail to develop normal stereocilia hair bundles required for sound perception.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of BET protein BRD4 has been investigated and characterized in the developmental processes of different cell types (Lee et al, 2017;Penas et al, 2019). BRD4 has been associated with HL in previous studies (de Souza et al, 2018;Olley et al, 2018), despite which, its role in HC development has not yet been studied. In this study, we provide evidence that Brd4 is necessary for the function and maintenance of the inner ear by studying a HC specific knock-out mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…17 Brd4 gene mutation may be associated with craniofacial malformations and auricle malformations. 18 Brd4 can also affect the development of the inner ear of mice, such as the absence of Brd4 in the inner ear of mice can lead to severe postnatal hearing loss. 19 According to the GO enrichment histogram analysis of differentially expressed mRNA source genes, the number of DEGs in the CC was the largest in E15.5 and E17.5, followed by MF.…”
Section: Discussionmentioning
confidence: 99%
“…Tcf12 controls the skull development and the growth rate of the skull during mouse embryonic development 17 . Brd4 gene mutation may be associated with craniofacial malformations and auricle malformations 18 . Brd4 can also affect the development of the inner ear of mice, such as the absence of Brd4 in the inner ear of mice can lead to severe postnatal hearing loss 19…”
Section: Discussionmentioning
confidence: 99%